2011
DOI: 10.1016/j.autneu.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Bezold–Jarisch reflex in sino-aortic denervated malnourished rats

Abstract: In this study we assessed the role of Bezold-Jarisch reflex (BJR) in the regulation of blood pressure (BP) of malnourished (MN) and control rats (CN) with sino-aortic denervation (SAD). Fischer rats were fed diets containing either 6% (MN) or 15% (CN) protein for 35 days after weaning. These rats underwent sham or SAD and catheterization of femoral artery and vein for BP measurements and drug injection. Phenylbiguanide (PBG 5 μg/kg, i.v.) for activation BJR, produced bradycardia (-317±22 bpm for CN vs. -372±16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 36 publications
2
16
2
Order By: Relevance
“…Animal studies have shown that absence of a balanced diet (i.e. low protein diets) can affect the sensitivity of these reflexes [5,34]. In our study, we showed that the Bezold-Jarisch reflex is compromised in rats under severe food restriction.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Animal studies have shown that absence of a balanced diet (i.e. low protein diets) can affect the sensitivity of these reflexes [5,34]. In our study, we showed that the Bezold-Jarisch reflex is compromised in rats under severe food restriction.…”
Section: Discussioncontrasting
confidence: 43%
“…Remarkably, other dietary challenges can also disrupt the cardiovascular regulatory mechanisms. In this regard, several studies have shown that post-weaning protein malnutrition, in rats, leads to changes in key systems involved in the regulation of systemic blood pressure [5]. Protein malnutrition causes an increased sensibility of the baroreceptor reflex, the chemoreflex [34] and the Bezold-Jarisch [40], a reflex from the heart and lungs that, when activated, leads the inhibition of sympathetic activity [4].…”
mentioning
confidence: 99%
“…This is indicated by the highly linear blood pressure increase in response to L-glutamate microinjection into the RVLM. However, in previous studies our group showed that an autonomic imbalance does occur in post-weaning protein-deprived rats (Martins et al, 2011;Bezerra et al, 2011a;Bezerra et al, 2011b). This lack of modulation of sympathetic activity by the RVLM may explain, in part, the autonomic imbalance observed in previous studies of our group.…”
Section: As Depicted Incontrasting
confidence: 38%
“…This lack of modulation of sympathetic activity by the RVLM may explain, in part, the autonomic imbalance observed in previous studies of our group. This autonomic imbalance in turn may contribute to the changes observed in the cardiovascular responses to activation of the barorefl ex (Loss et al, 2007), chemorefl ex (Penitente et al, 2007) and von Bezold-Jarisch refl ex (Bezerra et al, 2011a(Bezerra et al, , 2011b. It is well established in the literature that autonomic imbalance and cardiovascular neural refl ex impairment lead to hypertension and cardiovascular diseases.…”
Section: As Depicted Inmentioning
confidence: 99%
See 1 more Smart Citation